2002
DOI: 10.1046/j.1365-2672.2002.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a sewage treatment plant effluent on the faecal coliforms and enterococci populations of the reception river waters

Abstract: Aims: A rural sewage treatment plant and the effect of its effluent on the enterococci and faecal coliforms populations of the receiving river waters was evaluated. Methods and Results: The enumeration of bacteria was performed by membrane filtration. Diversity and population similarity were analysed using the PhP-plates system. The treatment plant reduces the number of enterococci and faecal coliforms to values similar to those observed upstream. All water samples showed a high diversity for both bacterial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
(9 reference statements)
3
10
0
1
Order By: Relevance
“…composition of faecal coliforms in the receiving river (Vilanova et al 2002). However, when the identification of resistant coliform species in raw and treated waters are made, significant differences are found in species composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…composition of faecal coliforms in the receiving river (Vilanova et al 2002). However, when the identification of resistant coliform species in raw and treated waters are made, significant differences are found in species composition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the disposal of treated sewage into rivers, lakes, or elsewhere may or may not influence environmental bacterial populations (Vilanova et al 2002). Some studies have found that wastewater treatment can raise or lower the proportions of antibiotic resistant bacteria which carry antibiotic resistance plasmids (Andersen, 1994;Ohlsen et al 2003).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…In this study, we used two types of plates specifically developed for typing of E. coli (PhP-RE plates) and enterococci strains (PhP-RF plates). The 11 substrates used for enterococci and E. coli have been described previously (24,30,51). The growth medium for PhP-RF contained 0.2% (wt/vol) proteose peptone (Oxoid), 0.05% (wt/vol) yeast extract (Oxoid), 0.5% (wt/vol) NaCl, and 0.011% (wt/vol) bromothymol blue, and for E. coli, it contained 0.1% (wt/vol) proteose peptone and 0.011% (wt/vol) bromothymol blue, according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A biochemical fingerprinting method known as the PhPlate system (PhPlate AB, Stockholm, Sweden) has been reported and used in many epidemiological and ecological studies (2,30,31,51). It measures the kinetics of bacterial metabolism in microtiter plates.…”
mentioning
confidence: 99%
See 1 more Smart Citation